FENOMENA PERNIKAHAN MUT’AH DI REPUBLIK ISLAM IRAN (Antara Ada dan Tiada) - Makmun, Sukron (IAIN Pekalongan, 2009)
This article is an observation for nearly four years in the land of the mullahs (Iran) as a country whose population is almost 80% are followers of Shia school, while the most prominent characteristics of the school is getting married mut’ah ‘. Among the ordinary people of Iran, the term is rarely used and tend mut’ah unpopular. They are more familiar with the term ‘sîgheh’. Mut’ah marriage is now rarely carried out by the Iranian society, even in the city itself as a city of Qom is the beginning of the Iranian revolution. They consider marriage mut’ah as part of the past and now no longer regarded as the Shiite tradition, but only as a scientific discourse alone